Rancangan Platform Pembelajaran Sejarah Lokal Berbasis Gamifikasi untuk Meningkatkan Keterlibatan Siswa di Era Digital - Agung Dwi Kurniawan; Aisyah Nurfadillah Adien; Eva Fauziah (PT. Willy Print Art, 2025)
History lessons play an important role in shaping students' character and national identity, including awareness of local history. However, in practice, history learning, especially local history, is still less popular because the presentation tends to be monotonous and based on memorization. This study aims to design a gamification-based online learning platform that can increase students' interest in learning local history in a more interactive and enjoyable way. The study used the Research and Development (R&D) method which focused on the design stage. The design results show that the characteristics of an effective platform include the integration of gamification elements such as points, badges, leaderboards, and reward and penalty systems through the